Super Efisiensi dan Analisis Sensitivitas Dea: Aplikasi pada Bank Umum Syariah di Indonesia - Rusydiana, Aam; Hasib, Fatin Fadhilah (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2020)
The framework for measuring the performance of Islamic banks is related to the concept of efficiency that has been widely implemented. However, there is a deficiency of the DEA model, especially in determining the best ranking of the DMU when there are several DMU units which are equally worth 1. In this study, Islamic banks in Indonesia were used as objects of study. After calculating the super efficiency, then the research will measure the level of influence of each variable on the relative efficiency value through sensitivity analysis. The results showed that, in super efficiency the highest value was owned by BSM bank in 2016 with a relative efficiency value of 1,351, followed by Bank Mega Syariah 2016 with 1,202 and BMI 2016 of 1,175. For sensitivity analysis, the efficiency value of Islamic banks was very sensitive to value output variables, especially operating income variables.